A Deep Embedding Model for Co-occurrence Learning - Shen, Yelong; Jin, Ruoming; Chen, Jianshu; He, Xiaodong; Gao, Jianfeng; Deng, Li (2015)
Co-occurrence Data is a common and important information source in many areas, such as the word co-occurrence in the sentences, friends co-occurrence in social networks and products co-occurrence in commercial transaction data, etc, which contains rich correlation and clustering information about the items. In this paper, we study co-occurrence data using a general energy-based probabilistic model, and we analyze three different categories of energy-based model, namely, the L , L and L models, which are able to capture different levels1 of2 dependencyk in the co-occurrence data. We also discuss how several typical existing models are related to these three types of energy models, including the Fully Visible Boltzmann Machine (FVBM) (L), Matrix Factorization (L), Log-BiLinear (LBL) models), and the Restricted Boltzmann Machine (RBM) model (L).2 Then, we propose a Deep Embedding Model (DEM) (an L model)k from the energy model in a principled manner. Furthermore,k motivated by the observation that the partition function in the energy model is intractable and the fact that the major objective of modeling the co-occurrence data is to predict using the conditional probability, we apply the maximum pseudo-likelihood method to learn DEM. In consequence, the developed model and its learning method naturally avoid the above difficulties and can be easily used to compute the conditional probability in prediction. Interestingly, our method is equivalent to learning a special structured deep neural network using back-propagation and a special sampling strategy, which makes it scalable on largescale datasets. Finally, in the experiments, we show that the DEM can achieve comparable or better results than state-of-the-art methods on datasets across several application domains.